Software watermarking: contributions that transcend the theme - Bento, Lucila; Boccardo, Davidson; Machado, Raphael; Simoes, Felipe; de Sá, Vinícius Pereira (Cadernos do IME - Série Informática, 2022)
Software watermarking is the embedding of data in the graphs that represent the execution of a computer program. Such structures are important technology tools, but also bring interesting combinatorial problems. In the present paper, we describe the advances in software watermarking during the last two decades, highlighting the important contributions of Prof. Jayme Szwarcfiter